Imagining Chinese medicine - Lo, Vivienne; Barrett, Penelope (Sir Henry Wellcome Asian studies, 2018)
A unique collection of 36 chapters on the history of Chinese medical illustrations, this volume will take the reader on a remarkable journey from the imaging of a classical medicine to instructional manuals for bone-setting, to advertising and comic books of the Yellow Emperor. In putting images, their power and their travels at the centre of the analysis, this volume reveals many new and exciting dimensions to the history of medicine and embodiment, and challenges eurocentric histories. At a broader philosophical level, it challenges historians of science to rethink the epistemologies and materialities of knowledge transmission. There are studies by senior scholars from Asia, Europe and the Americas as well as emerging scholars working at the cutting edge of their fields. Thanks to generous support of the Wellcome Trust, this volume is available in Open Access.